A Review of Black Widow (Araneae: Theridiidae) Envenomation, Epidemiology, and Antivenom Utilization in Canada. Issue 1 (15th August 2020) - Curran-Sills, Gwynn; Wilson, Steven M; Bennett, Robb
Abstract: Two species of black widow spider (BWS— Latrodectus hesperus Chamberlin & Ivie and Latrodectus variolus Walckenaer) naturally occur in Canada and are capable of causing deleterious envenomation to humans. No Canadian literature exists on the frequency of envenomations by these species or the use of antivenom in the treatment of those patients. A review of primary Canadian arachnology data was undertaken to identify BWS populations. A retrospective review of the Health Canada Special Access Program records generated epidemiology and the utilization of antivenom for BWS envenomations in Canada. The geographical distribution of BWS species is limited to along the southern Canadian border. From January 2009 to December 2015, there were five BWS envenomations that required treatment with antivenom and all cases occurred in British Columbia. An average patient age of 41 yr ± 21 SD (range 7–59) was observed, along with three of the five patients being female. The average number of vials used for treatment was 2 ± 1 SD (range 1–3). BWS Antivenin was also obtained by facilities in Alberta, Ontario, and Nova Scotia, but not used in any of these jurisdictions. Further investigation is necessary to determine the annual incidence of BWS envenomations and if treatment with BWS antivenin is required.